2006
DOI: 10.1021/bi0612667
|View full text |Cite
|
Sign up to set email alerts
|

On the Seeding and Oligomerization of pGlu-Amyloid Peptides (in vitro)

Abstract: Oligomerization of amyloid beta (Abeta) peptides is the decisive event in the development of Alzheimer's disease (AD), the most common neurogenerative disorder in developed countries. Recent evidence links this conformation-driven process to primary- and secondary-structure modifications of Abeta. The N and C terminus of deposited Abeta has been shown to possess conspicuous heterogeneity. While the C-terminally longer form of Abeta, i.e., Abeta (42), is considered more amyloidogenic, the role of the N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
240
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 247 publications
(260 citation statements)
references
References 37 publications
13
240
1
2
Order By: Relevance
“…N-terminal deletions generally enhance aggregation of ␤-amyloid peptides in vitro (53). Additionally, A␤ pE3 is known to have a high aggregation propensity (54,55), increased stability (56), enhanced toxicity compared with fulllength A␤ (57), and dramatically reduced solubility at physiological pH-conditions (58). Our findings go along with the A␤ pE3 seeding hypothesis (20,54,57).…”
Section: Discussionsupporting
confidence: 68%
“…N-terminal deletions generally enhance aggregation of ␤-amyloid peptides in vitro (53). Additionally, A␤ pE3 is known to have a high aggregation propensity (54,55), increased stability (56), enhanced toxicity compared with fulllength A␤ (57), and dramatically reduced solubility at physiological pH-conditions (58). Our findings go along with the A␤ pE3 seeding hypothesis (20,54,57).…”
Section: Discussionsupporting
confidence: 68%
“…Studies showed that pyroglutamate Aβ [AβN3(pE)] contributed substantially to AD pathology because of its high neurotoxicity and abundance in AD brains (53,54). To investigate whether CRANAD-3 can interact with AβN3(pE), we performed fluorescence spectral testing similar to experiments with other Aβs.…”
Section: Resultsmentioning
confidence: 99%
“…Pyroglutamate variant A␤3(pE)-42 and to a lesser extent A␤11(pE)-42 are a predominant A␤ species in AD plaques (2-4, 10, 52), and together with other N-and C-terminally truncated A␤ species, they are also formed in plaque-free brains of healthy individuals aged at least 70 years (6). Moreover, because A␤3(pE)-42 forms aggregation seeds 250-fold faster than unmodified A␤ (53) it may trigger antibody responses at very low concentrations long before pathological changes are observed in the brain. Indeed, human plasma in general showed high reactivity against pyroglutamate-modified peptides such as A␤3(pE)-42, A␤11(pE)-42, but only low reactivity against unmodified A␤11-42 ( Fig.…”
Section: Discussionmentioning
confidence: 99%